2019
DOI: 10.1111/poms.12902
|View full text |Cite
|
Sign up to set email alerts
|

Status Goods and Vertical Line Extensions

Abstract: C onspicuous consumption of status goods signals consumers' status and grants status value to them. In this article, we examine how firms selling status goods make vertical line extension decisions when they take consumers' status preferences into account. Analyzing an incumbent's vertical line extensions when it faces a threat of entry, we find that status preferences can make unprofitable extensions profitable. Moreover, without status preferences, an incumbent can introduce line extensions to crowd out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Literature Review. This study adds to the growing stream of research that incorporates consumers’ psychological and social behavior in quantitative models to examine optimal firm decisions (see e.g., Jain and Li 2018, Li 2019, Li and Jain 2016, Lim 2010, and Lim and Ho 2007). This stream of research enriches traditional economic models with psychological realism and provides new insights.…”
Section: Introductionmentioning
confidence: 99%
“…Literature Review. This study adds to the growing stream of research that incorporates consumers’ psychological and social behavior in quantitative models to examine optimal firm decisions (see e.g., Jain and Li 2018, Li 2019, Li and Jain 2016, Lim 2010, and Lim and Ho 2007). This stream of research enriches traditional economic models with psychological realism and provides new insights.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also contributes to a growing body of literature in operations management on luxury goods (e.g., Chiu et al. 2018, Li 2019, Li and Liu 2019). Their foci are on firm strategies in branding luxury goods whereas our focus is on a consumer's willingness to pay for different types of signals attached to luxury goods.…”
Section: Introductionmentioning
confidence: 55%
“…While an extensive literature has shown that, in general, strong brand signals are preferred and influential in consumers' purchasing decisions (e.g., Erdem andSwait 1998, Rao et al 1999), our findings suggest that, in the luxury goods market, a quiet brand signal may be preferred to a loud brand signal. Our study also contributes to a growing body of literature in operations management on luxury goods (e.g., Chiu et al 2018, Li 2019, Li and Liu 2019. Their foci are on firm strategies in branding luxury goods whereas our focus is on a consumer's willingness to pay for different types of signals attached to luxury goods.…”
Section: Introductionmentioning
confidence: 80%
“…Conspicuous consumption of status products signals the owner's wealth and social status, thereby providing status Production and Operations Management benefits for consumption (Bagwell & Bernheim, 1996;Belk, 1988;Veblen, 1934). We follow Rao and Schaefer (2013) to formulate consumers' status utility from consuming status products (for similar use, see Gao et al, 2016;Li, 2019). We describe the formulation of status utility for buyers and nonbuyers and explain the rationale behind it.…”
Section: Status Utilitymentioning
confidence: 99%